FDI inflow effects on Western Balkan area's labour markets - Peric, Milica; Stanišić, Nemanja (The European Journal of Applied Economics, 2020)
Economic growth and labour market dependency on Foreign Direct Investments (FDI) inflow is very high in transition economies. This paper estimates the effects of FDI inflow on the employment rate and average net wages in Western Balkan economies in the period 2003–2017. The sample of economies was selected mainly because of the high legacy with FDI and unsaturated labour market. Presumably FDI inflow have positive impact on the employment rate and on average net wages in the Western Balkan countries. Employing linear mixed-effects models (LMM), the results indicate that FDI inflow changes has very low but positive and significant effects on the both changes in employment rate and in average net wages.
Keywords: average net wage; employment rate; foreign direct investments; linear mixed models; random effects